Ethnomathematics Eksploration of The Traditional Game of Congklak - Nurzahro Tusolihah; Muhamad Ali Misri; Indah Nursuprianah (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2022)
Congklak is a traditional game that has a long history and contains philosophies in its development. The aim of this study is to explore congklak from ethnomathematics side so that they can know the cultural value of traditional congklak games and their connection to mathematics, describe the mathematical elements contained in congklak and to find out the role of congklak in mathematics learning. This research uses qualitative research approach with type of ethnographic research supported by literature research methods. Data collection techniques that researchers do use interviews, observations, documentation, and literatur studies. This research instrument is the researcher himself using recorder aids, cameras, and stationery. The results of ethnomathematic exploration in traditional congklak games are seen from the mathematical elements, namely there are arithmetic, geometry, graphs, and probability. Cultural elements in congklak are honesty (sportive), accuracy, patience, and sharing. Congklak in mathematic learning act as ethnomatematics-based learning media. The results of this study are as information for teachers to make congklak as a medium of mathematics learning both as conventional and digital gamesÂ